Diagnosing Performance of Matrix Metalloproteinase-9 (MMP-9) and Alberta Stroke Program Early CT Score (ASPECTS) as The Clinical Degree Predictor of Ischemic Stroke: Which One is Better ? - Ashaeryanto; Muhammad Akbar; Muhammad I. Basri; Gita V. Soraya; Ashari Bahar; Cahyono Kaelan (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Matrix metalloproteinase-9 (MMP-9) and Alberta Stroke Program Early CT Score (ASPECTS) are predictors of the ischemic stroke clinical degree. A marker with good performance is needed to estimate the clinical degree following an ischemic stroke attack. Puropose(s): Analyze the comparison of MMP-9 levels with ASPECTS as a predictor of the clinical degree of ischemic stroke. Methods: Analytical study with a prospective cohort design. This study sample consisted of middle cerebral artery ischemic stroke patients at RSUP Dr. Wahidin Sudirohusodo and Network Hospital with a total of 32 patients. The MMP-9 level was measured by using the ELISA method, while ASPECT was assessed based on the head CT scan. Clinical degree assessment according to the National Institute of Health Stroke Scale (NIHSS). Spearman and Receiver Operating Characteristic (ROC) tests were performed to determine sensitivity and specificity. Results: ASPECTS sensitivity and specificity values on NIHSS admission: 85.71% and 90.91%, NIHSS day 14: 70.37% and 100%. Sensitivity and specificity of MMP-9 on NIHSS admission: 72.73% and 76.19%, NIHSS day 14: 100% and 70.73%. Conclusion: ASPECTS has a stronger specificity level than MMP-9 as a predictor of the pure clinical degree of ischemic stroke, and MMP-9 has a stronger sensitivity value than ASPECTS as a predictor pure clinical degree day 14.